Community-Based Waste Management: Backwater Tourism as a Case Example - Emilda K Joseph; Tomy K Kallarackal and Bindi Varghese (Atna, J Tour Stud, 2017)
A healthy environment is essential for the growth of Tourism industry. The future of tourism is inevitably related to the environment. As important natural resources, backwaters should be preserved in a sustainable manner. SWM emerged as an essential for keeping tourist destination clean and livable. This paper analyses the community-based waste management process in one of the famous backwater tourist destinations of Kerala and explains the roles and activities of all stakeholders and their relationship at the community level. This paper also helps to identify the reasons for CBWM and justify its need for community participation. It is based on semi-structured interviews and direct observation conducted on the research area.Regardless of efforts to improve community involvement in waste management there is a lack of comprehension and understanding in the participation of community level stakeholders.